The empty envelope - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 1998)
Dink and his friends unearth the mysterious truth behind the envelopes incorrectly delivered to his house.
"A Stepping Stone book."
2-4.
500
Keywords: Letters -- Fiction; Mystery and detective stories